Intraventricular immune checkpoint inhibition with nivolumab in relapsed primary central nervous system lymphoma - Kaulen, Leon D.; Gumbinger, Christoph; Hinz, Felix; Keßler, Tobias; Winkler, Frank; Bendszus, Martin; Sahm, Felix; Wick, Wolfgang (Neuro-oncology advances, 2022)
Sequencing studies have deciphered the genetic landscape of primary central nervous system lymphoma (PCNSL) paving novel therapeutic avenues in recent years.1,2
Gesehen am 09.06.2022